Bahasa Adang di Pulau Alor: Kajian Vitalitas Etnolinguistik - NFN Inayatusshalihah; Miranti Sudarmaji (Badan Pengembangan dan Pembinaan Bahasa, 2020)
Language use is a critical indicator for ethnolinguistic vitality. The greater the number of domains where a language used, the stronger a language. This study aims to examine the vitality of Adang language in Adang Buom, Teluk Mutiara District, Alor Regency based on indicator of language use. The Adang use is observed in five domains such as home, religion, transaction, education, government and health institution. Data are collected using questionaire and analyzed within ethnolinguistic vitality theory. This study finds that the number of Adang domains amongst Adang Buom community has decreased. Adang is used in conjuction with Indonesian (or Malay-alor), both in private and public domains. The young generation tends to use Indonesian (or Malay-Alor) in home domain. Based on the indicator of language use, Adang could be categorized as a language with dwindling domains. Trend in Indonesian usage amongst Adang community is motivated by communicative, economic, prestigious, and religious motivations.AbstrakPenggunaan bahasa dalam ranah merupakan indikator penting vitalitas etnolinguistik. Sebuah bahasa yang digunakan di ranah yang beragam akan memiliki daya hidup yang kuat. Kajian ini bertujuan untuk mengukur tingkat daya hidup bahasa Adang di Adang Buom, Kecamatan Teluk Mutiara, Kabupaten Alor berdasarkan indikator penggunaan bahasa. Penggunaan bahasa Adang dilihat dalam lima ranah, yaitu rumah, ibadah, transaksi, pendidikan, dan institusi pemerintahan dan kesehatan. Data kajian dikumpulkan dengan menggunakan kuesioner dan dianalisis dengan teori vitalitas etnolinguistik. Hasil kajian menunjukkan jumlah ranah penggunaan bahasa Adang dalam komunitas tutur Adang Buom mengalami penyusutan. Bahasa Adang digunakan bersamaan dengan penggunaan bahasa Indonesia (atau Melayu-Alor), baik di ranah yang bersifat pribadi maupun publik. Generasi muda cenderung menggunakan bahasa Indonesia (atau Melayu-Alor) di ranah rumah dengan keluarga. Dari indikator penggunaan bahasa, Adang dapat dikategorikan sebagai bahasa dengan ranah yang berkurang atau dwindling domains. Adanya kecenderungan penggunaan bahasa Indonesia di kalangan komunitas Adang didorong oleh motivasi komunikatif, ekonomi, prestisius, dan religius.